Reconceptualizing Human Capital Through Multicentric Digital Governance & Cross-Border Synchronization - Ramjit, Dana-Marie (Contemporary Public Administration Review, 2025)
This paper interrogates the transformation of human capital governance under the accelerating energies of digital globalization and technological innovation. It identifies a central governance problem: existing institutional arrangements are increasingly inadequate to address the ethical, distributive, and social challenges posed by algorithmic systems, digital platforms, and data-driven decision-making. While prior research has explored digital governance in areas such as e-government and automation, little attention has been paid to how these dynamics are reshaping human capital governance as a multi-scalar and ethically charged domain. The purpose of this study is to analyze these transformations and advance the concepts of multicentric digital governance and cross-border synchronization, which reconceptualize workforce governance as an adaptive, pluriversal, and participatory process. The discussion highlights the dual challenge of leveraging digital tools to enhance efficiency and inclusion while mitigating risks such as bias, commodification, and inequality. The paper concludes by outlining policy solutions that balance innovation with principled oversight, offering a framework for building resilient, equitable, and ethically grounded structures of human capital governance in the digital age. The conceptual framework advanced in this study offers insights for the broader governance and organizational studies literature, illustrating how digitalization reshapes authority, ethics, and stakeholder engagement across sectors.